Association of 30-s Sit-to-Stand Power Test Outcome With Body Balance in Physically Active Older Adults. - Monteiro, Pedro Henrique Martins; Valenciano, Paola Janeiro; Mendes, Pedro Henrique Silva; Teixeira, Luis Augusto (Journal of Aging & Physical Activity, 2025)
Amount of serial sitting and standing movements has been employed in clinical and research settings to assess legs' muscular strength. In this cross-sectional study, we aimed to test the correlation between the 30-s sit-to-stand power test (30STS) outcome and body balance in older adults. We evaluated physically active male and female (n = 51) individuals with an age range of 60–80 years (M = 69.29). Participants were assessed on the maximum number of repetitions for 30STS and on the performance of balance tasks, as follows: quiet standing in unipedal support, unipedal support while alternately touching two targets on the ground with the toe of the nonsupporting foot in either the anteroposterior (AP) or mediolateral (ML) direction, and paced sit-to-stand supported on a narrow bipedal support base. Performance on the balance tasks was measured through smartphone-based triaxial trunk accelerometry (meters per second squared), with analysis made through root mean square for the AP and ML axes. Analysis indicated significant negative correlation coefficients of 30STS outcome with trunk acceleration on unipedal quiet stance tasks both in the ML (r = −.46) and AP (r = −.40) directions and with the AP alternate target touching task for ML trunk acceleration (r = −.34) and the ML alternate target touching task for AP trunk acceleration (r = −.31). These results suggest that in active older adults, the 30STS outcome is associated with balance in unipedal quiet standing and dynamic tasks. Our findings indicate the contribution of balance control in the performance of 30STS.